Fostering social inclusion in Islamic elementary schools: Teacher support, peer interaction, and religious values - Amelia Rizki Ardianti; Calista Amalia Setiaji; Choiriyah Widyasari; Minsih Minsih (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2025)
Inclusive education extends beyond physical access to schooling and requires meaningful social participation among all learners, including students with special needs. In Islamic elementary schools, inclusive practices are further shaped by religious values that emphasize compassion, justice, and collective responsibility. However, empirical evidence remains limited on how social interactions are enacted in everyday classroom life and how teacher support operates within faith-based inclusive settings. This study aims to examine how social interactions between students with special needs and their peers manifest in inclusive Islamic elementary schools and to analyze the role of teacher support in shaping the form, quality, and sustainability of these interactions. Using a qualitative ethnographic approach, data were collected over six months through participant observation, in-depth interviews with teachers, students, and parents, and document analysis in three inclusive Islamic elementary schools in Kartasura, Indonesia. Data analysis followed the Miles and Huberman interactive model, involving data reduction, data display, and conclusion drawing. The findings reveal that social interaction is highly context dependent, with more frequent and reciprocal engagement occurring during structured learning activities, while unstructured situations such as recess remain vulnerable to social exclusion. Teacher support emerged as a decisive factor in fostering inclusion through emotional reassurance, instructional scaffolding, and social mediation, particularly when grounded in Islamic values such as rahmah (compassion), cooperation, and moral responsibility. The study concludes that teachers function as key agents of social inclusion in Islamic elementary schools, and that culturally grounded, sustained teacher support is essential for strengthening peer acceptance and meaningful participation. These findings offer important implications for teacher preparation, inclusive pedagogy, and policy development in faith-based educational contexts.